Framing Analysis Of Political Survey News Coverage In Klikers Media - Putri, Vinna Yuliana; Narti, Sri; SM, Anis Endang (Utami Publisher, 2025)
This study aims to analyze the construction of reality in political survey news coverage published by the online media Klikers. The researcher adopts Robert N. Entman's (1993) framing analysis approach, which comprises four key elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. The study focuses on two Klikers articles reporting on electability surveys ahead of Indonesia's 2024 presidential election. A qualitative descriptive method was employed, with data collected through observation, documentation, and literature review. The findings indicate that Klikers consistently frames the presidential candidate pair Prabowo-Gibran in a positive narrative, emphasizing their strong electability and effective campaign strategies. This framing contributes to shaping public opinion in favor of their political legitimacy. However, the lack of transparency regarding survey methodology and source balance suggests potential bias in news construction. The study highlights the importance of media literacy in the digital information era and the relevance of framing analysis in revealing media bias within the realm of political communication.